Mental Fitness And Psychological Resilience And Their Relationship To Achievement Level In Fencing Students At Al-Qasim Green University - Ali Nazar Mohi; Israa Razzaq Chafat; Ahmed Hassan Ghdhaib (Journal Sport Science Indonesia, 2026)
Fencing students face many difficulties that occur during lessons to varying degrees, and repeated exposure to it, can lead to a student losing motivation to win and being unable to withstand such challenges. One of the researchers is a fencing instructor encountered such difficulties, which became increasingly apparent during exams. The researchers attribute decline in performance to weaknesses in mental fitness and psychological resilience is a crucial factor in achieving optimal performance among combatants, because combatants face numerous situations, including flow state of fight physical and technical exertion required under greater pressure. This necessitates increased effort, greater endurance, and ability to confront challenges with maximum intensity. Consequently, researchers have focused on studying relationship between these two variables and students fencing performance. This study aimed to develop measures of mental fitness and psychological resilience, recognizing reality of mental fitness and psychological resilience and level of achievement among students in fencing, identify relationship between mental fitness, achievement level and psychological resilience. The most important conclusions were sample members have very good levels of both mental fitness and psychological toughness in fencing for third-year students in Colleges of Physical Education at Al-Qasim Green University, there is a significant correlation between mental fitness and level of achievement in fencing, and also between psychological toughness and level of achievement in fencing, there is a correlational relationship between mental fitness and psychological toughness with level of achievement in fencing for third-year students in faculties of physical education at Al-Qasim Green University.